“Baixou o santo” no reino dos céus: a relação dialética entre a Umbanda e a Igreja Universal do Reino de Deus - Carvalho, Bruna David de (2018)
The Brazilian religious field is plural, full of nuances and from this, there are phenomena that must be studied within its specificities, as is the case of the relation between Umbanda and the Universal Church of the Kingdom of God. The main objective of this work is to analyze the elements that constitute this relationship through its historical, symbolic and ritualistic aspects. In addition, this is justified, therefore, the dialectic of this relationship has brought unfoldings to the religious field and its parameters can be used for the study of other phenomena. The hypothesis raised is that the fundamental aspects of this relationship are reflexes of mentalities present in Brazil, generally of a prejudiced and intolerant nature, marginalizing people because of their individualities. This work was constituted, first through the proper discourses of the religions with works that seek to systematize their experiences, which gives that the religious phenomenon express itself. Moreover, through the theoretical reference, based on the human sciences, we have brought the analysis of the constitutive elements of these religions and the construction of their relation. Therefore, the result was the obtaining of a panorama of the constitution and consolidation of this relationship in the religious field, through approximations and resignifications, as well as other factors that, based on their complexity, guarantee their particularity